The effect of mothers training program based on the PRECEDE model on the prevention of growth retardation in children (6-12 months) at health centers in Shiraz, Fars Province - Kashfi, Seyed Mansor; Khani jeihooni, Ali; Rezaianzade, Abbas; Babaei Heydarabadi, Akbar (Archives of Advances in Biosciences, 2013)
Growth retardation in children is a result of nutritional ignorance, inappropriate care, and lack of growth monitoring. This study was performed to assess the effect of mothers training program, based on the PRECEDE model, on the prevention of growth retardation in 6-12 months old children. This quasi experimental study was conducted on 120 mothers (60 in the experimental and 60 in the control group) with single child and exclusively on breast feeding who were cared by health centers in Shiraz, Fars province. The data were gathered through a questionnaire which included demographic characteristics, the components of the PRECEDE model (knowledge, attitude, enabling as well as reinforcing factors, and maternal function) and child weight. Educational intervention was performed during 6 sessions each of which lasted for 55 to 60 minutes. The questionnaire was completed by the experimental group before and 4 months after the training program. The results showed that the educational intervention program in the experimental group caused significant increase in the means of knowledge score (P<0.001) and attitude score (P<0.001). This study showed that enabling and reinforcing factors (and training sessions), performance score of mothers as well as weight of children among experimental group were significantly higher than control group (p=0.01). The results of this study indicated that mothers training program based on the PRECEDE model was highly effective on the prevention of growth retardation in the study population.